2016
DOI: 10.1002/chem.201600202
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Magnet Behavior of Individual Polyoxometalate Molecules Incorporated within Biopolymer or Metal–Organic Framework Matrices

Abstract: The chemically and structurally highly stable polyoxometalate (POM) single-molecule magnet (SMM) [(FeW9 O34 )2 Fe4 (H2 O)2 ](10-) (Fe6 W18 ) has been incorporated by direct or post-synthetic approaches into a biopolymer gelatin (Gel) matrix and two crystalline metal-organic frameworks (MOFs), including one diamagnetic (UiO-67) and one magnetic (MIL-101(Cr)). Integrity of the POM in the Fe6 W18 @Gel, Fe6 W18 @UiO-67 and Fe6 W18 @MIL-101(Cr) composites was confirmed by a set of complementary techniques. Magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 89 publications
0
26
0
Order By: Relevance
“…Such materials have shown their efficiency for catalytic reactions ranging from the oxidation of alkylbenzene (Sun et al, 2016 ) to the C-H activation of nitrile (Shi et al, 2016 ) and water oxidation (Mukhopadhyay et al, 2018 ; Paille et al, 2018 ). Interestingly, it has also been shown that a single-molecule magnet iron POM isolated in the cavities of a diamagnetic MOF preserves its magnetic properties (Salomon et al, 2016 ). Besides, while Ln-MOFs and Ln-doped MOFs have been largely studied, the encapsulation of a well-defined inorganic luminescent compound in MOFs for sensing and detection has been rarely described (Cui et al, 2015 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such materials have shown their efficiency for catalytic reactions ranging from the oxidation of alkylbenzene (Sun et al, 2016 ) to the C-H activation of nitrile (Shi et al, 2016 ) and water oxidation (Mukhopadhyay et al, 2018 ; Paille et al, 2018 ). Interestingly, it has also been shown that a single-molecule magnet iron POM isolated in the cavities of a diamagnetic MOF preserves its magnetic properties (Salomon et al, 2016 ). Besides, while Ln-MOFs and Ln-doped MOFs have been largely studied, the encapsulation of a well-defined inorganic luminescent compound in MOFs for sensing and detection has been rarely described (Cui et al, 2015 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, heterogeneous catalytic processes are preferred, as they allow easier catalyst recovery and recycling, which is of significant industrial interest. One well‐explored strategy to convert homogeneous POM catalysts to heterogeneous ones revolves around their encapsulation within porous solid supports, such as porous oxides and metal–organic frameworks (MOFs) . MOFs are particularly well‐suited as host materials for POMs owing to their crystalline open structures, varying pore volumes and surface areas, tunable functionality, and, in certain cases, high thermal, chemical, and hydrolytic stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…116 Thus, the internal magnetic field created by the long-range magnetic ordering of the MOF seems to have an influence on the slow magnetic relaxation of the SIM leading to an attenuation of the quantum tunneling of the magnetization in the mononuclear complex. Non-magnetic MOFs have also been used to accommodate the magnetic molecules with 118 In the diamagnetic matrix the SMM behavior is retained because the magnetic anisotropy of the POMs is not altered by their interaction with the host. Differently, in the antiferromagnetic matrix the SMM character is clearly reduced because the magnetic interactions lead to faster relaxation of the magnetization.…”
Section: Sco@mofsmentioning
confidence: 99%